Civil Service as Public Servant: Responsive, Reliable, and Adaptive to Digital Technology - Arifin, Antoni Ludfi; Solihin, Dadang; Murni, Sylviana (Monas: Jurnal Inovasi Aparatur, 2024)
The Civil Servant (ASN) plays a crucial role in improving the quality of public services in Indonesia. This study aims to analyze service-oriented ASN from the aspects of responsiveness, reliability, and the use of information technology in delivering public services. The methodology employed is a literature review, utilizing more than 50 scholarly articles and other relevant academic sources. The findings indicate that a service-oriented ASN is characterized by responsiveness, reliability, and effective use of digital technology in striving to provide services that satisfy the public. ASN’s responsiveness to public complaints, consistency in service delivery, and use of e-government as an effective communication tool contribute to public trust. This study provides recommendations for government agencies to continuously develop ASN competencies, streamline bureaucratic procedures, and leverage information technology for more efficient and transparent service delivery.